The Effects of Air Pollution on Mortality in Socially Deprived Urban Areas in Hong Kong, China - Wong, Chit-Ming (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Poverty is a major determinant of population health, but little is known about its role in modifying air pollution effects. OBJECTIVES: We set out to examine whether people residing in socially deprived communities are at higher mortality risk from ambient air pollution. METHODS: This study included 209 tertiary planning units (TPUs), the smallest units for town planning in the Special Administrative Region of Hong Kong, China. The socioeconomic status of each TPU was measured by a social deprivation index (SDI) derived from the proportions of the population with a) unemployment, b) monthly household income < US$250, c) no schooling at all, d) one-person household, e) never-married status, and f ) subtenancy, from the 2001 Population Census. TPUs were classified into three levels of SDI: low, middle, and high. We performed time-series analysis with Poisson regression to examine the association between changes in daily concentrations of ambient air pollution and daily number of deaths in each SDI group for the period from January 1996 to December 2002. We evaluated the differences in pollution effects between different SDI groups using a case-only approach with logistic regression. RESULTS: We found significant associations of nitrogen dioxide, sulfur dioxide, particulate matter with aerodynamic diameter < 10 μm, and ozone with all nonaccidental and cardiovascular mortality in areas of middle or high SDI (p < 0.05). Health outcomes, measured as all nonaccidental, cardiovascular, and respiratory mortality, in people residing in high SDI areas were more strongly associated with SO(2) and NO(2) compared with those in middle or low SDI areas. CONCLUSIONS: Neighborhood socioeconomic deprivation increases mortality risks associated with air pollution.